Preparation, characterization, and application of Pd-SnO sensors as an electronic nose in peruvian wine classification and its comparison with chromatographic techniques - Paredes-Doig A.L. (2018)
SnO-based sensors doped with palladium (0, 1, 3, 5 and 7%) were prepared by the wet impregnation method. To characterize them, the techniques ofinfrared spectroscopy with Fourier transform (FTIR), adsorption and desorption of N2 (BET), XRD, scanning electron microscopy (SEM), and X-ray dispersive energy (EDX) spectroscopy were used. The sensors were evaluated with ethanol to form, together with two commercial sensors, an electronic nose (E-nose) that could detect volatile aroma components in Peruvian wines. The results were interpreted through principal component analysis (PCA) to find a technique that complemented the information collected by gas chromatography (GC) and liquid chromatography (HPLC), and by comparing the PCAs obtained from GC, and HPLC with those resulting from E-nose. It was found that the latter classified the samples better. It was possible to differentiate both wines from the same grape and from a different strain, and to detect adulterated wines, which contributes to the wine industry in controlling its production to improve the quality of this drink for the consumer. © 2018, Universidad Nacional de Colombia. All rights reserved.